ANALYSIS OF SPORTS RESULTS FOR THE RUNNING EVENTS OF THE 2022-2023-2024 WINTER UZBEK CHAMPIONSHIP AND CUP COMPETITIONS - Olimov M.S. (Proximus Journal Publishing, 2024)
This article provides data studied on the basis of a comparative analysis of the sports results of the final stage of the men's 400-800-1500 m event at the 2022-2023-2024 Winter Uzbek Championship and cup competitions in athletics. The dynamics of these obtained sports results are covered in the cross section of years based on the diagram and conclusions are drawn. The reasons for the decline in results and suggestions for its elevation have been given
Keywords: sports results; athlete; athletics